Perancangan Sistem Kearsipan Dokumen Digital Berbasis Web (Studi Kasus: Jakarta Nanyang School): Perancangan Sistem Kearsipan Dokumen Digital Berbasis Web - JURI PEBRIANTO (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
−Increasingly rapid progress of technology and ease of access for the use of such technology, bringing the idea to use research to help in archiving digital documents. To accommodate the needs of workers who need access to the digital document data faster. Should the existence of a centralized storage so that processing and storage of all office data can be more efficient. For the system information to be stored and easily accessed anytime quickly, it would require a database server that can store data and information that has been entered into the application. The information in the database in addition to catering for all employees. Information system development archiving using Agile methods of software development is most appropriately used to build an application that involves the client and the developer or programmer in all respects, because of the addition of features and add-on applications will be implemented quickly with good communication between the client and the programmer. Making web-based application programming using PHP with MySQL is used as the database server. The response and feedback from the clients also authorizes the improvement and development of this information system. Keywords: Information systems, archive, digital document, website, server, agile software development, PHP, MYSQL.